Microbiota Manipulation by Probiotics Administration as Emerging Tool in Cancer Prevention and Therapy - Panebianco, Concetta; Latiano, Tiziana; Pazienza, Valerio (Frontiers in Oncology, 2020)
A growing body of literature indicates that microbiota plays a significant role in the development and curability of cancer, essentially due to microbial ability to modulate immune and inflammatory responses to cancer and therapeutic treatments. Probiotics consumption, either in the form of food or supplements, is an easy and feasible way to manipulate microbiota composition and a number of recent researches have shown that it may represent a valid approach to prevent cancer onset and progression, to improve the clinical efficacy of the current anticancer treatments and to mitigate the harmful adverse events of chemo- and radiotherapy, which often lead to scale drug doses, to delay or interrupt treatments. In this review we gather the main in vivo studies on the current topic, focusing on the beneficial effects and underlying mechanisms provided by bacterial and yeast probiotics and their combination, in the setting of various types of cancers and different therapeutic protocols. These findings will likely open the way to consider, in the next future, regular probiotics intake as an adjuvant strategy in cancer prevention and management.